Equivalent servings of free-range reindeer promote greater net protein balance compared to commercial beef - Coker, Melynda S. (Int J Circumpolar Health, 2021)
Wild game consumption has been associated with health benefits but the acute influence on human protein metabolism remains unknown. We compared feeding-induced responses of equivalent amounts of free-range reindeer (FR) and commercial beef (CB) on protein kinetics using stable isotope methodology. Seven participants (age: 40 ± 14 years; body mass index: 24 ± 3 kg/m(2)) completed two randomised studies, ingesting 2 oz of FR or CB. L-[ring (2)H(5)]phenylalanine & L-[ring (2)H(2)]tyrosine were delivered via primed, continuous intravenous infusion. Blood samples were collected during the basal period and following consumption of FR or CB. Feeding-induced changes in whole-body protein synthesis (PS), protein breakdown (PB), and net protein balance (NB) were determined via plasma sample isotope enrichment analysis by gas chromatography-mass spectrometry; plasma essential amino acid (EAA) concentrations were determined by liquid chromatography-electrospray ionisation-mass spectrometry. Plasma post-prandial EAA concentrations were higher with FR compared to CB (P < 0.05). The acute feeding-induced PS response was not different, but PB was reduced and contributed to a superior level of NB (P < 0.00001) in FR compared to CB. Our results demonstrate that FR may influence more favourable protein metabolism than CB. These data support potential health benefits of wild game onf whole-body protein. Abbreviations: BMI: body mass index; DIAAS: digestible indispensable amino acid score; CB: commercial beef; EAA: essential amino acids; FR: free-range reindeer; R(a): rate of appearance; UAF: University of Alaska Fairbanks; USDA: USA Department of Agriculture